Student Motivation in Computer Networking Courses - Wen-Jung Hsin, PhD (Park University, 2007)
This paper introduces several hands-on projects that have been used to motivate students in learning various computer networking concepts. These projects are shown to be very useful and applicable to the learners' daily tasks and activities such as emailing, Web browsing, and online shopping and banking, and lead to an unexpected byproduct, self-motivation.